2021
DOI: 10.1021/acs.jmedchem.1c01094
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibition of Nicotinamide N-Methyltransferase by Alkene-Linked Bisubstrate Mimics Bearing Electron Deficient Aromatics

Abstract: Nicotinamide N -methyltransferase (NNMT) methylates nicotinamide (vitamin B3) to generate 1-methylnicotinamide (MNA). NNMT overexpression has been linked to a variety of diseases, most prominently human cancers, indicating its potential as a therapeutic target. The development of small-molecule NNMT inhibitors has gained interest in recent years, with the most potent inhibitors sharing structural features based on elements of the nicotinamide substrate and the S -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…They refer to studies where silenced NNMT has resulted in decreased migration, invasion, proliferation, and increased chemosensitivity [ 50 ], and also that NNMT expression is enhanced in cancer stem cells [ 51 ]. The NNMT enzyme takes a methyl group from S-adenosyl-L-methionine (SAM) and adds it to nicotinamide (NA), generating methyl-nicotinamid (MNA) and S-adenosyl-L-homocysteine as a result [ 52 ]. It is believed that it would decrease the methylation capacity of the methionine cycle towards the DNA/histone methylation path, causing aberrant methylation, which could lead to cancer progression in the case of the overexpression of NNMT.…”
Section: Discussionmentioning
confidence: 99%
“…They refer to studies where silenced NNMT has resulted in decreased migration, invasion, proliferation, and increased chemosensitivity [ 50 ], and also that NNMT expression is enhanced in cancer stem cells [ 51 ]. The NNMT enzyme takes a methyl group from S-adenosyl-L-methionine (SAM) and adds it to nicotinamide (NA), generating methyl-nicotinamid (MNA) and S-adenosyl-L-homocysteine as a result [ 52 ]. It is believed that it would decrease the methylation capacity of the methionine cycle towards the DNA/histone methylation path, causing aberrant methylation, which could lead to cancer progression in the case of the overexpression of NNMT.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies on larger cohorts of patients are needed to confirm these findings and to explore the biological role of NNMT in HNT. Moreover, this enzyme could be a promising target for cancer therapy, which can be studied in more detail thanks to the development of specific NNMT inhibitors which have shown promising results in preclinical studies [ 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of writing, the specificity of these inhibitors for NNMT over other methyltransferases has yet to be published. Our most recent inhibitor, (S)-2-amino-4((((2R,3S,4R,5R)-5-(6-amino-9H-purin-9-yl)-3,4-dihydroxytetrahydrofuran-2-yl)methyl)((E)-3-(4-cyanophenyl) allyl)-amino)butanoic acid (compound 17u), replaces the nicotinamide mimic common in current bisubstrate inhibitors with an electron-deficient para-cyano aromatic group coupled with a trans-alkene linker, resulting in an IC 50 of 1.7 nM [222]. Inhibitor selectivity studies revealed that compound 17u has 3000-fold higher activity towards NNMT than PNMT.…”
Section: Bisubstrate Inhibitorsmentioning
confidence: 99%